Occupations associated with diabetes complications: A nationwide-multicenter hospital-based case-control study. (April 2022) - Nakazawa, Shoko; Fukai, Kota; Furuya, Yuko; Kojimahara, Noriko; Hoshi, Keika; Toyota, Akihiro; Tatemichi, Masayuki
Highlights: Diabetes patients in certain occupations had higher risks of diabetes complications. Service workers had higher risks of all subtypes of diabetes complications. Longest and recent occupations resulted in the same trends. Abstract: Aim: Investigating the risks of diabetes complications among inpatients with diabetes associated with longest-held and current occupations. Method: Using a Japanese nationwide, multicenter, hospital inpatient dataset (2005–2015), a matched case-control study with 39, 550 inpatients with diabetes was conducted. We considered both the longest-held and current occupations of the study subjects. Result: Diabetes complications such as retinopathy, nephropathy, neuropathy, and peripheral vascular complications occur more often in managers, sales workers, service workers, transportation workers, construction and mining workers and carrying, cleaning and packing workers. Among these occupations, particularly the service workers indicated consistently significant increased risks (OR = 1.36 (1.23–1.51)) in developing all the considered subtypes of diabetes complications, and the performed sensitivity analysis confirmed this conclusion. Moreover, among service workers, cooks, waiters, building service staff and other service workers were identified as having the highest risks in developing diabetes complications (ORs = 1.30 (1.12–1.51), 1.63 (1.36–1.95), 1.79 (1.21–2.67), and 2.05 (1.30–3.22), respectively). Conclusions: Our study's potential translational impact should lead to subsequent investigations on the causes connected to certain occupations of various diabetes complications and particularly to more carefully dealing with patients with diabetes who work in the identified occupational areas and their health risks.